2017
DOI: 10.22598/mt/2017.29.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Information Systems Integration, Innovation and Consumer-Based Commitment Practices for Knowledge Sharing in Creating Power Brands

Abstract: Purpose-The purpose of this paper is to focus on establishing a relationship between the level of consumer commitment through knowledge sharing and what sustains innovation in SMEs through the integration of information systems to build power brands. Design/Methodology/Approach-Several procedures were used to empirically determine the study: a) the Harman one-factor test; b) the common latent factor approach; c) the confi rmatory factor-analytic approach to the Harman one-factor test. Findings and implications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The publication trend has grown steadily since, reaching a maximum of twelve publications in 2018. Among 45 articles, the recent ones are from 2017 (Amidi et al, 2017;Edwards et al, 2017;Hitchen et al, 2017;Okazaki et al, 2017;Panda & Deepa, 2017;Shen & Guangyan, 2017; Soto-Acosta & Palacios-Marques, 2017; Świgoń, 2017), 2018 (Chang, 2018;Das & Mahapatra, 2018;Esin, 2018;Hood, 2018;Kumi & Sabherwal, 2018;Lu, Zhou, & Chen, 2018;Park & Gabbard, 2018;Sedighehm & Ainin, 2018;Septiani & Ave, 2018;Zhang, Liu, Deng, & Chen, 2018) and 2019 (Nisar, Prabhakar, & Strakova, 2019;Tayebi, Manesh, Khalili, & Sadi-Nezhad, 2019;Kim, Gibbs, & Scott, 2019 etc. ) The rising trend indicates a growing interest in the field of knowledge sharing on social media, but also its infancy.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The publication trend has grown steadily since, reaching a maximum of twelve publications in 2018. Among 45 articles, the recent ones are from 2017 (Amidi et al, 2017;Edwards et al, 2017;Hitchen et al, 2017;Okazaki et al, 2017;Panda & Deepa, 2017;Shen & Guangyan, 2017; Soto-Acosta & Palacios-Marques, 2017; Świgoń, 2017), 2018 (Chang, 2018;Das & Mahapatra, 2018;Esin, 2018;Hood, 2018;Kumi & Sabherwal, 2018;Lu, Zhou, & Chen, 2018;Park & Gabbard, 2018;Sedighehm & Ainin, 2018;Septiani & Ave, 2018;Zhang, Liu, Deng, & Chen, 2018) and 2019 (Nisar, Prabhakar, & Strakova, 2019;Tayebi, Manesh, Khalili, & Sadi-Nezhad, 2019;Kim, Gibbs, & Scott, 2019 etc. ) The rising trend indicates a growing interest in the field of knowledge sharing on social media, but also its infancy.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…However, this is possible only with gained customers' trust, just like in the aforementioned case of travel and destination knowledge. For example, a recent study by Panda and Deepa (2017) investigated relationships between consumers' knowledge sharing and innovation in small and medium companies through the integration of social media. The study, consequently, proved the increasing significance of loyalty related to the knowledge sharing on social media.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Luhn et al (2017) and Vayrynen et al (2017) found that SMEs use internal tools to support innovation. Panda and Kapoor (2017), Benitez et al (2018) and Scuotto et al (2017) explored social media data for the creation of knowledge and innovation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Innovation is generally described as a catalyst for businesses to keep pace with market changes and drive customer satisfaction, loyalty and performance [5]. The literature explains that in an agile global marketplace where consumers seek better value, innovation is essential for customer satisfaction and loyalty [6]. Scholars in the area of innovation have further mentioned that businesses can use innovations strategically to compete in local and global markets [7].…”
Section: Introductionmentioning
confidence: 99%